Perception Of Maydolongnons In The Wearing Of Facemask (Journal of Namibian Studies : History Politics Culture, 2023)
The study was conducted to determine the perception level of Maydolongnons on the wearing of face mask. The unit analysis of the study was the 222 residents in the Poblacion Barangays of Maydolong E. Samar who serve as respondents. The study focuses on perception level of the respondents towards wearing a face mask and was measured by 5-point Likert scale categorized under; comfort, efficacy doubt, access, compensation, inconvenience, appearance, attention, and independence. Descriptive survey method was used in this study. To obtain the needed data the researchers distributed a questionnaire to the respondents. The data were tabulated, analyzed and interpreted. Findings of the study revealed that the perception of Maydolongnons on wearing facemask mostly remark as “neither agree nor disagree”. This means, that respondents had the sense of impartiality on their beliefs and behaviors in the wearing of facemask.